Formation of Toxic Oligomeric α-Synuclein Species in Living Cells - Outeiro, Tiago Fleming (Public Library of Science, 2008)
BACKGROUND: Misfolding, oligomerization, and fibrillization of α-synuclein are thought to be central events in the onset and progression of Parkinson's disease (PD) and related disorders. Although fibrillar α-synuclein is a major component of Lewy bodies (LBs), recent data implicate prefibrillar, oligomeric intermediates as the toxic species. However, to date, oligomeric species have not been identified in living cells. METHODOLOGY/PRINCIPAL FINDINGS: Here we used bimolecular fluorescence complementation (BiFC) to directly visualize α-synuclein oligomerization in living cells, allowing us to study the initial events leading to α-synuclein oligomerization, the precursor to aggregate formation. This novel assay provides us with a tool with which to investigate how manipulations affecting α-synuclein aggregation affect the process over time. Stabilization of α-synuclein oligomers via BiFC results in increased cytotoxicity, which can be rescued by Hsp70 in a process that reduces the formation of α-synuclein oligomers. Introduction of PD-associated mutations in α-synuclein did not affect oligomer formation but the biochemical properties of the mutant α-synuclein oligomers differ from those of wild type α-synuclein. CONCLUSIONS/SIGNIFICANCE: This novel application of the BiFC assay to the study of the molecular basis of neurodegenerative disorders enabled the direct visualization of α-synuclein oligomeric species in living cells and its modulation by Hsp70, constituting a novel important tool in the search for therapeutics for synucleinopathies.